Indian economy since independence : chronology of events - Behari, Madhuri; Behari, Bepin (Delhi : D.K. Publications : distributed by D.K. Publishers' Distributors, 1983)
(Chronological events, 1947-1982; on the economic programs and policies; includes Indian economic statistics)
Bibliography: p. 283-296.
mizan
Keywords: India -- Economic policy -- 1947- -- Chronology